FERROMAGNETISM AND SUPERCONDUCTIVITY IN URANIUM COMPOUNDS - Matthias, B. T. (1969)
The intimate correlation between the mechanisms causing magnetism and superconductivity in uranium compounds has been verified again—in novel systems.